(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
Тhe article reveals the classification of computational transactions of foreign economic activity of economic entities in the account of export-import transactions, problem solutions, changes and regulations in the Export-import sphere in our country today, and gives conclusions and suggestions within the framework of the topic.